RHETORIC IN THE ENGLISH AND RUSSIAN LANGUAGES - Mukhammetkharisova, Albina Ilgizovna (Educational Research in Universal Sciences, 2023)
In this article discusses about rhetoric in the English and Russian languages and given some important information about them